Determinants of Gastritis Occurrence in The Working Area of Telaga Dewa Health Center, Bengkulu City in 2024 - Nuvriyanti, Liza; Habibi, Julius; Surahman, Fery; Darmawansyah, Darmawansyah; Suyanto, Jipri (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
Intoduction: According to the World Health Organization (WHO), the highest prevalence of gastritis occurrence in the world is found in Canada at 35%. Based on the health profile of Indonesia in 2019, Indonesia ranks third in the highest cases of gastritis in Asia, after India and Thailand, with a fairly high prevalence of gastritis at 274,396 cases or 40% of the population of 238,452,952 people. From the data of the Bengkulu Provincial Health Office in 2022,there were still many cases of gastritis recorded as the third most common disease in Bengkulu Province, with a total of 51,069 cases. The Telaga Dewa Health Center reported the highest incidence of gastritis, with 1,689 cases recorded from patient visits in 2022.The purpose of this study is to determine the relationship between dietary patterns, stress, and knowledge with the occurrence of gastritis in the working area of Telaga Dewa Health Center, Bengkulu City in 2024. Method: The method used is a descriptive correlational research design with a cross-sectional approach, using purposive sampling technique. Data were collected by distributing questionnaires to 90 individuals representing all respondents in the working area of Telaga Dewa Health Center, Bengkulu City, based on inclusion and exclusion criteria. Result and Discussion: The results of the study showed that there is a relationship between dietary patterns and the occurrence of gastritis with a p-value of 0.000, a relationship between stress and the occurrence of gastritis with a p-value of 0.001, and a relationship between knowledge and the occurrence of gastritis with a p-value of 0.000. Conclusion: his study concludes that there is a relationship between dietary patterns, stress, and knowledge with the occurrence of gastritis in the working area of Telaga Dewa Health Center, Bengkulu City.